ANALISIS KELAYAKAN FINANSIAL AGROFORESTRI PT. SUMATERA ALAM ANUGERAH SUMATERA SELATAN - Delfy Lensari; Yayat Hidayat; Abdul Latief (Universitas Tanjungpura, 2021)
Agroforestry systems produced a variety of products with different harvested periods, where at least one type of product takes more than one year to grow. PT SAA owns land planted with an Agroforestry cropping pattern. The plants planted are Sengon and Pineapple. Agroforestry systems have economic advantages. To see the extent to which an agroforestry business provides economic benefits, the most suitable analysis to be used is a project analysis based on finance. For that it was necessary to conduct a financial feasibility analysis. The purpose of this study was to analyze the financial feasibility of agroforestry with sengon and pineapple cropping patterns at PT. Sumatra Alam Anugerah. The data processing method is using the quantitative method. The analysis uses the NPV, BCR, BEP, PBP calculation method. The results showed that financially the agroforestry business was feasible to run because it produced an NPV of Rp. 3,516,185,198. For sengon plants and Rp. 722,733,233. The NPV produced by pineapple plants with the BCR value of sengon plants was 4.86 and 37.06, the BCR value produced by pineapples. The breakeven point value or BEP and payback periode for sengon plants occurs in year 5 and for pineapple plants in year 1 (one).